Increased Expression of Tumor Proliferation Genes in Hispanic Women with Early-Stage Breast Cancer. (21st November 2014) - Kalinsky, Kevin; Lim, Emerson A.; Andreopoulou, Eleni; Desai, Avni M.; Jin, Zhezhen; Tu, Yifan; Hibshoosh, Hanina; Wang, Antai; Greenlee, Heather; Crew, Katherine D.; Maurer, Matthew; Sparano, Joseph A.; et al.
Abstract : Hispanic women have higher breast cancer mortality compared to non-Hispanic whites. We evaluated for Proliferation Axis Score differences, as determined by Onco type Dx, in Hispanic and non-Hispanic white women with newly diagnosed breast cancer. We matched 219 women, based upon age, stage, and nodal status. Compared to non-Hispanic whites, Hispanic women with hormone-sensitive, HER2-negative early-stage breast cancer had a higher Proliferation Axis Score. No differences were seen in Recurrence Score, ER, PR, or HER2 by Onco type DX. CCNB1 and AURKA were significantly higher in Hispanic women. These tumor differences may help explain breast cancer outcome differences between the two ethnicities.